Pengaruh Word of Mouth, Harga dan Kualitas Produk terhadap Keputusan Pembelian - Dinda Bintang Anjani; Wahju Wulandari; Mulyono Mulyono (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Word of Mouth, price, and product quality on consumer purchasing decisions at Kopi Studio 24 in Malang City, both simultaneously and partially, and to identify the most dominant variables. The approach used in this study is quantitative with the explanatory research method. The population in this study were all customers of Kopi Studio 24, with the sampling technique using purposive sampling. The number of respondents in this study was 100 people. Data collection was carried out by distributing questionnaires to customers who had made purchases at Kopi Studio 24. The questionnaire instrument was compiled based on the indicators of each research variable and tested for validity and reliability. Data analysis was carried out using multiple linear regression with the help of SPSS software version 25. The results of the study showed that the variables Word of Mouth, price, and product quality simultaneously had a positive and significant effect on purchasing decisions. Partially, the three variables also had a positive and significant effect. Among the three, Word of Mouth was the variable that had the most dominant influence on consumer purchasing decisions. This shows that word of mouth, whether through personal experience, friend recommendations, or reviews on social media, plays an important role in encouraging consumers to purchase products at Kopi Studio 24. This finding implies that Kopi Studio 24 managers need to strengthen their Word of Mouth-based marketing strategy and maintain product quality and set competitive prices to increase consumer purchasing decisions.